Mediating role of information technology infrastructure support on the influence of human capital determinants towards the technical and vocational education and training institutions - Farahiyah Akmal binti Mat Nawi
The compatibiIity 'person-organisation' is a crucial focus to the sustainabiIity of higher education institution and has been clearly highlighted in Malaysia Education Blueprint 2015-2025 (Higher Education). Technical and Vocational Education and Training (TVET) has acts as one of the important driver to accomplish the country's education objective. Subsequently, as the institution's 'capital' TVET lecturers have become a key resource. Therefore, their professional profile needs to be consolidated in parallel with the education ecology. Apart from that, technology infrastructure is also seen as a signifIcant tool in boosting the quality of TVET education where the chalk and paper method is no longer relevant in current environment. This study reports on the role of ability, education, experience, knowledge, skill and training as the determinants of human capital and its significant contribution towards the institution performance. Technological infrastructure supports also been assessed as the mediator to examine its affect towards performance. A theoretical model was underpinned by the theory of Human Capital (HC), Resource Based View theory and Malcolm Baldrige Criteria for Performance Excellence, which consist of six independent constructs, one mediating construct and one dependent construct. A comprehensive investment in human capital is necessary for the lecturers to become flexible to achieve a sustainable growth trend. Some issues have been discussed regarding the quality of TVET lecturers such as shortage of qualified, skill gaps, lack of industrial exposure and pedagogical knowledge. A quantitative study has been carried out to gather the feedback oflecturers from 9 polytechnic campuses in the East Coast, Malaysia. An adapted survey consisting of 63 items with 7 Likert scale was distributed to 1478 of TVET lecturers and 398 samples were successfully collected using the Stratified Sampling procedure. The data were then analysed using the Structural Equation Modelling (SEM) approach on SmartPLS3 platform to test the hypotheses. The results confirmed the hypotheses in determining the direct and significant effect between the constructs. Skill was identified as the key driver of the significant relationship of HC towards the TV T institution performance (t =2.126, p=0 .143, p- value=0. 016). The result revealed that skill, knowledge and training had significant and positive relationship towards the performance. While the mediating testing resuIted, technological support is signiflcantly influencing the institution performance. Mainly, this study has made significant contribution to help the Ministry in recognising the main determinants, to accelerate TVET performance. Study results provide supp0l1 to the importance of sustaining the key determinants of human capital and its management for competitive advantage at institutional and national level.